ASYMPTOTIC FREEDOM: A POSSIBLE PHYSICAL EXPLANATION - puccini, Antonio (European Journal of Applied Sciences, 2020)
The Quarks asymptotic freedom phenomenon is characterized by a certain movement independence of the quarks(Qs) but only for very short distances. This derives from the fact that when Qs are very close together, the Strong Interaction(SI) almost completely loses its strength. Why? It could be assumed that this is a consequence of the shielding and masking effects in their turn supported by the congruous and elegant mathematical formalism of the Quantum Chromo-Dynamics, sufficient on its own to explain the phenomenon. On the other hand we wonder: what is the objective, physical, concrete reality that underlies it? What is the exact physical mechanism for which the SI strength is not homogeneous throughout its action radius? Or: how can Qs, alone, without any help, have enough strength and power to get rid of the extremely intense grip exercised by the SI? Unless there is the intervention of some other phenomena, currently unknown, completely unrelated to the SI. Then, one might wonder: is it possible that there is something between the Qs, which at first goes unnoticed, but when the particles gather each other excessively this something begins to be felt, showing a clear and energetic repulsive action? But if so, what is it? We believe that in the asymptotic freedom it is not the SI to loose strength, but it is overwhelmed by another force, a Repulsive Force, quite distinct from it, and that, in certain peculiar circumstances, proves to be even more powerful than the SI itself.